Penerapan Model Pembelajaran Kepala Bernomor Struktur Untuk Meningkatkan Tanggung Jawab Siswa Pada Muatan Pembelajaran PPKn di Kelas V SD Babussalam - Nur Asiah (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2024)
This study aimed to investigate students' increased responsibility for the content of civics education instruction in Grade 5 of Babussalam Elementary School, Pekanbaru Province. The reason for this study was students' lack of responsibility for preparing for their studies in advance, making effective use of their time, completing individual assignments, and seriously participating in discussions. It was action research in the classroom. The subjects of this study were teachers and 17 fifth grade students from Babusalam Primary School Pekanbaru. The goal was to implement a "structured numbered head" learning model and hold students accountable. The study was conducted over two cycles, and each cycle included two meetings. Perception and documentation were the ways to obtain information. The process of information analysis was a clear check with the rate. Based on research findings and information checks, it has been shown that organized numbered leader degree programs have higher degree requirements. This is evidenced by the fact that the second degree requirement existed before the activity and was below 74% in the poor category. After the educational activities were carried out in the first cycle, the second learning requirement increased to 76%, and in the very good category it was between 74% and 82%. It increased to 83% in the second cycle and ranged from 83% to 91% at high speed. It is legitimate to conclude that his second learning requirement regarding the content of civics lessons in the 5th review of Babus Salam Primary School Pekanbaru can be expanded through the use of a structured numberhead learning program.